Risk of smoking-related cancers among women and men living with and without HIV. (1st January 2021) - Hessol, Nancy A.; Barrett, Benjamin W.; Margolick, Joseph B.; Plankey, Michael; Hussain, Shehnaz K.; Seaberg, Eric C.; Massad, L. Stewart
Abstract : Objectives: We investigated whether the effect of smoking on the incidence of smoking-related cancers differs by HIV-infection status, if sex modifies the impact of risk factors for smoking-related cancers, and the sex-specific attributable risk of smoking on cancer incidence. Design: Data from two large prospective studies in the United States were analyzed: 6789 men in the Multicenter AIDS Cohort Study from 1984 through 2018 and 4423 women in the Women's Interagency HIV Study from 1994 through 2018. Methods: Incidence rates, relative risks, and adjusted population attributable fractions (PAFs) were calculated for smoking-related cancers. Results: During study follow-up, there were 214 incident smoking-related cancers in the men and 192 in the women. The age-adjusted incidence ratess for smoking-related cancers were higher in the women (392/100 000) than for the men (198/100 000; P  < 0.01) and higher for people living with HIV (PLWH, 348/100 000) than for those without HIV (162/100 000; P  < 0.01). Unadjusted incidence rates in PLWH were higher than in those without HIV when stratifying by cumulative pack-years of smoking (all P values <0.01). In adjusted interaction models, the effects of cumulative pack-years of smoking were significantly stronger in women. The adjusted PAFs for smoking-related cancers were nonsignificantly higher in the women than in the men (39 vs. 28%; P  = 0.35). Conclusion: HIV looks to be an independent risk factor for smoking-related cancers and women appear to have a greater risk than men. These results highlight the need for interventions to help PLWH, especially women, quit smoking and sustain cessation to reduce their risk of smoking-related cancers. Abstract : Supplemental Digital Content is available in the text